Comprehensive approach to controlling chronic hepatitis B in China - Shan, Shan; Zhao, Xinyan; Jia, Jidong (Clinical and molecular hepatology, 2024)
Hepatitis B virus (HBV) infection was highly endemic in China, where the prevalence of HBsAg was 9.7% in 1992. Comprehensive strategies, including universal infant hepatitis B vaccination with emphasis on timely birth-dose and 3-dose coverage, dramatically reduced the mother-to-infant transmission and early childhood acquisition of HBV, resulting in estimated HBsAg prevalence rates of 5.6% and 0.1% in the general population and among children aged <5 years in 2022, respectively. Clinical guidelines on the prevention and treatment of chronic hepatitis B have been periodically updated based on emerging evidence from clinical research. The continuously improved reimbursement policy and the massively reduced price of antiviral drugs through government negotiation and central procurement have increased treatment accessibility and affordability. However, due to the low rates of diagnosis and treatment, China still faces a large challenge in achieving the 2030 goal of lowering HBV-related mortality by 65%. A public health approach involving concerted efforts from the government, medical community, industry, and society as a whole would be necessary to increase the uptake of HBV tests and treatment to achieve the global goal of eliminating viral hepatitis as a public health threat by 2030.